Clinical characteristics of 50 hepatocellular adenoma patients among 164 cases of glycogen storage disease type Ia - Xu, Yiwen; Liu, Yan; Yuan, Yuheng; Hong, Yuehui; Ma, Mingsheng; Pan, Jie; Wei, Min; Qiu, Zhengqing (European journal of pediatrics, 2025)
Hepatocellular adenoma (HCA) can occur in patients with glycogen storage disease type Ia (GSDIa), which is caused by mutations in the glucose-6-phosphatase gene (G6PC). Studies on HCA in GSDIa patients are limited and show variable results. Larger cohorts of GSDIa patients with HCA should be investigated. In this study, we examined the clinical characteristics and G6PC genotypes of 50 patients with HCA among 164 GSDIa cases. The incidence of HCA in GSDIa patients was 30.5% and increased with age. The mean age of HCA onset was 16.5 ± 4.4 years. The median age of GSDIa patients with HCA who received uncooked cornstarch treatment was significantly older than that of patients without HCA (14 years (11, 16.5) vs. 3 years (1, 9), p = 0.000). Median plasma triglyceride levels significantly decreased after treatment with uncooked cornstarch (5.36 mmol/L (3.44, 8.73) vs. 8.35 mmol/L (5.44, 13.27), p = 0.004). The most common G6PC genotype in GSDIa patients was [c.648G > T] + [c.648G > T]. The incidence of the G6PC [c.648G > T] + [c.248G > A] genotype was significantly lower in GSDIa patients with HCA compared to that in GSDIa patients without HCA (2.0% (1/49) vs. 14.7% (16/109), p = 0.018). Some HCAs with small diameters may temporarily disappear. Conclusion: Special attention should be paid to the occurrence of HCAs in GSDIa patients, particularly during adolescence. Earlier initiation of uncooked cornstarch treatment may reduce the incidence or delay the onset of HCAs by lowering triglyceride levels. Small and stable HCAs can be closely followed up since they may disappear temporarily.